Study on high efficient sapphire wafer processing by coupling SG-mechanical polishing and GLA-CMP. (August 2018) - Xu, Yongchao; Lu, Jing; Xu, Xipeng; Chen, Chao-Chang A.; Lin, Yujing
Abstract: A novel surface finish process sequence has been developed with a sequential process employing sol-gel (SG) semi-fixed abrasive polishing tool and gas-liquid assisted chemical mechanical polishing (GLA-CMP) instead of general copper-resin lap or plate (CP) and chemical mechanical polishing (CMP) to enhance the surface finishing efficiency for sapphire wafer. The surface and subsurface quality of sapphire wafer after the SG and GLA-CMP process have been compared with those by CP and CMP, respectively. Results show that the SG polishing can offer a better surface quality in terms of both surface roughness and sub-surface damage for the next fine polishing step. Based on the contact mechanics models, yielding effects of the SG polishing pad are found to be effective to scratch mitigation. This trend is consistent with experimental results. Furthermore, oxygen is applied as catalyst to improve the removal material rate (MRR) of sapphire by GLA-CMP. It is found that oxygen concentration can improve MRR of sapphire polishing. Among four combinations of CP, SG, CMP, and GLA-CMP, the machining by coupling SG and GLA-CMP shows the maximum MRR approximately as high as 77.6 nm/min, more than 10.23% larger than that of CP-machined wafer and traditional CMP. Ultra-smooth wafer surface with damage-free can be achieved by this new process sequence and the sapphire wafer with qualified surface can be obtained within 50 min by GLA-CMP, which is 90 min shorter than the original 140 min polished by the conventional CMP method. Compared to the conventional surface finish process sequence, the proposed sequence shows superior processing efficiency and quality for sapphire wafers. Highlights: A novel surface finish process sequence has been proposed for sapphire wafer. Yielding effect model of abrasives was developed in terms of pad properties. Abrasive penetration depth changes inversely with matrix hardness of plate. Oxygen is effective to improve the remove rate of sapphire in GLA-CMP.